Facilitating Adjustment: Sector Experiences from Agriculture, Telecommunications and Chemicals - Engman, Michael (OECD Trade Policy Papers, 2006)
This paper is a follow-up study to Trade and Structural Adjustment: Embracing Globalisation (OECD 2005) which identified policies for successful trade-related structural adjustment. It draws further policy implications through the analysis of three sectors which were not specifically/fully covered in the initial report: agriculture (tobacco and coffee), telecommunications and...